Inter-rater reliability of wound care skills checklist in objective structured clinical examination - Abdillah, Ina Laela; Nurjannah, Intansari (International Journal of Research in Medical Sciences, 2016)
Background: The wound care skills checklist in objective structured clinical examination (OSCE) should be valid and reliable. Thus, the reliability test of the wound care skills checklist is needed. Purpose of the study was to identify the reliability of the wound care skills checklist. Methods: This study is a descriptive non-experimental quantitative research with a cross-sectional study design. This study was conducted in the School of Nursing, Universitas Gadjah Mada, Indonesia. The number of respondents was 94 second-year students of this school of nursing. Inter-rater reliability was performed by 2 raters during OSCE. Kappa and Percent agreement (PA) were used to analyze the reliability of the checklist. Results: Inter-rater reliability of the wound care skills checklist is categorized as good based on kappa value (0.7613) and acceptable based on PA value (89.36%). The results of the twenty-two item checklist were divided into five categories. Sixteen of the twenty-two items on the wound care skills checklist are included in the first category in which kappa category (≥0.41) and PA (>70%) are acceptable. One item is in the second category which has unacceptable value of kappa and PA, one item is in the third category which has low kappa value (0.3974) and high PA (89.36%), one item is in the fourth category which has a kappa value of 0, and three items are in the fifth category which has negative kappa value. Conclusions: Inter-rater reliability of the wound care skills checklist OSCE in this nursing school can be categorized as good and acceptable.